Sustainable procurement policies and practices in BAPEX's project management to the SDGs - Amin, Mohammad Ahsanul (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2023.